2019
DOI: 10.3892/ol.2019.10034
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol induces p53 in colorectal cancer through SET7/9

Abstract: Resveratrol is one of the most promising phytoalexins for use as an anti-cancer agent, which is present in the skin of red grapes and berries. Resveratrol has been demonstrated to modulate a number of signalling pathways that are involved in carcinogenesis. In the present study, the function of resveratrol as a pro-apoptotic agent in colorectal cancer cell lines, including HCT116, CO115 and SW48, was investigated. The results revealed that resveratrol supressed cell viability. Additionally, resveratrol enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 33 publications
3
29
0
Order By: Relevance
“…The results of in silico experiments suggest the capability of resveratrol to interact with these enzymes in the micromolar range. The docking calculations were also consistent with multiple in vitro studies highlighting inhibitory effects of resveratrol and its analogs on colon cancer cell viability in both basal and pro-inflammatory conditions [36][37][38]. docking calculations were also consistent with multiple in vitro studies highlighting inhibitory effects of resveratrol and its analogs on colon cancer cell viability in both basal and pro-inflammatory conditions [36][37][38].…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The results of in silico experiments suggest the capability of resveratrol to interact with these enzymes in the micromolar range. The docking calculations were also consistent with multiple in vitro studies highlighting inhibitory effects of resveratrol and its analogs on colon cancer cell viability in both basal and pro-inflammatory conditions [36][37][38]. docking calculations were also consistent with multiple in vitro studies highlighting inhibitory effects of resveratrol and its analogs on colon cancer cell viability in both basal and pro-inflammatory conditions [36][37][38].…”
Section: Resultssupporting
confidence: 78%
“…The results of in silico experiments suggest the capability of resveratrol to interact with these enzymes in the micromolar range. The docking calculations were also consistent with multiple in vitro studies highlighting inhibitory effects of resveratrol and its analogs on colon cancer cell viability in both basal and pro-inflammatory conditions [36][37][38].…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Increasing evidence has proven the antitumor effect of resveratrol. Notably, in human hepatocellular carcinoma cells, resveratrol suppressed invasion of cells through inhibition of tumor necrosis factor-α-mediated matrix metalloproteinase 9 (MMP9) expression (Yu et al, 2008) and caused cell cycle arrest via the activation of the p53-dependent pathway in colorectal cancer (Liu et al, 2019). These lines of evidence significantly suggested that stilbenes are promising candidates for tumor therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol (3,4′,5 tri-hydroxystilbene) (C14H12O3) is a natural polyphenol compound found in various plants and herbs, including blueberries, raspberries, mulberries, and the skin of grapes [173]. Resveratrol has anti-inflammatory and antiproliferative properties, as well as antitumor effects on various human cancers [93,174], including prostate [113,175], thyroid [176], colorectal [177,178], breast [179,180], lung [181,182], and bladder cancers [93,95,111,113,183]. Resveratrol inhibits the AR signaling pathway in prostate cancer by affecting PCGEM1 and PRNCR1 [107,108,109,110].…”
Section: Introductionmentioning
confidence: 99%